THE ROLE OF ENVIRONMENTAL TAXATION IN PROMOTING ECOLOGICAL SAFETY AND STRATEGIC DEVELOPMENT OF THE RUSSIAN FEDERATION - L. S. Samodelko (Вестник университета)
Environmental taxation contributes to the development of relations between the state and taxpayers. Trends in the development of the environment taxation confirm and justify its role in ensuring environmental safety and strategic development of the Russian Federation as one of the economic methods of the state regulation. By methods of comparative analysis, synthesis, grouping of data, problems in the field of effective use of tax instruments to improve the environmental situation have been revealed, as well as priority areas for the development of environmental taxation in Russia have been determined.